(untitled) (Research, Society and Development, 2023)
The objective of this article was to carry out a literature review on oral lesions in patients admitted to the Intensive Care Unit (ICU). Scientific articles were selected in the databases: PUBMED and LILACS, written in English or Portuguese, published from 2000 to 2023. Opinion articles and clinical cases were excluded. The terms used for the search were: “intensive care unit”, “COVID-19” AND “oral diagnosis” OR “oral health”. The results describe that patients admitted to the ICU are routinely admitted with a poor oral condition, which can be aggravated during the hospitalization time and contribute to the worsening of the individual’s prognosis. Several studies have already demonstrated the importance of oral hygiene in the prevention of nosocomial pneumonia, but few describe the oral condition of patients in the ICU. Among the clinical findings of oral health in ICU patients are accumulation of oral biofilm and tongue coating, periodontal disease, candidiasis, ulcers, dental abscesses and residual roots. The presence of oral lesions in hospitalized patients demonstrates the importance of Hospital Dentistry’s role in the prevention, diagnosis and treatment of these lesions, which worsen the patient’s quality of life and can be a gateway to secondary infections. In addition, more research is needed to describe the oral alterations of hospitalized patients and their possible correlation with the individual’s general health.